Gersonides' afterlife : studies on the reception of Levi ben Gerson's philosophical, Halakhic and scientific oeuvre in the 14th through 20th centuries - Elior, Ofer; Freudenthal, Gad; Wirmer, David (Studies in Jewish history and culture, 2020)
"Gersonides' Afterlife is the first full-scale treatment of the reception of one of the greatest scientific minds of medieval Judaism: Gersonides (1288-1344). An outstanding representative of the Hebrew Jewish culture that then flourished in southern France, Gersonides wrote on mathematics, logic, astronomy, astrology, physical science, metaphysics and theology, and commented on almost the entire bible. His strong-minded attempt to integrate these different areas of study into a unitary system of thought was deeply rooted in the Aristotelian tradition and yet innovative in many respects, and thus elicited diverse and often impassionate reactions. For the first time, the twenty-one papers collected here describe Gersonides' impact in all fields of his activity and the reactions from his contemporaries up to present-day religious Zionism"--